Outbreak of Coccidiosis in 5-day Old Commercial Broiler Breeder Flock in Zaria, Nigeria - Musa, I.W.; Saidu, L.; Jatau, I.D.; Adamu, J.; Otu, M.O.; Abdu, P.A. (International Journal of Poultry Science, 2010)
Field outbreaks of coccidiosis all over the world were commonly reported in chickens over 3-weeks of age. Outbreak of coccidiosis in birds in the first few weeks of life is becoming increasing important but chickens less than 1-week of age appeared not to be susceptible. This case report describes the clinical signs and gross lesions of coccidiosis as well as its microscopic appearance in a five-day old intensively managed broiler breeder chicks. The outbreak occurred in December, 2009 and was characterized by early onset of an acute disease with high mortality. Other clinical features of the disease were: progressive increase and sudden decline of high chick mortality of up to 50%, ruffled feathers, blood stained whitish to brownish diarrhea, weakness and anorexia. Gross lesions seen were congested carcasses, distended caeca and intestinal segments with blood, mucus and tissue debris; retained yolk sac was also observed in some birds. Whole intestines were submitted to the Protozoology and retained yolk sac to Microbiology Laboratories for investigations. A farm visit revealed very poor housing ventilation and wet litter. Laboratory results confirmed coccidian schizonts and gametocytes from caeca and intestinal scrapings. Escherichia coli was isolated from the yolk sac. High hygienic standards must be maintained in hatcheries and poultry houses, damp and warm litter must be avoided and adequate ventilation should always be provided in poultry houses to prevent coccidiosis.